1977
DOI: 10.1111/j.1432-1033.1977.tb11668.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of N‐Glycolylneuraminic Acid in Porcine Submandibular Glands

Abstract: 1. The morphology of porcine submandibular gland tissue is demonstrated by light and electron microscopy.2. Subcellular particles from porcine submandibular glands were prepared by a procedure adapted to the presence of viscous mucus, and were fractionated on continuous and discontinuous sucrose gradients.3. Six particulate fractions were obtained by discontinuous gradient centrifugation. These were identified by electron microscopy, marker enzymes and nucleic acid content and were designated as follows: (1) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…For instance, Rearick et al [q have reported the characterization of porcine submaxillary P-galactoside a2 +3-sialyltransferase, to form the sequence NeuAca(2-t 3)-Galfl(1+3)GalNAc, although this structural element had not been reported in porcine submaxillary mucin (PSM). In addition, a study by Sherblom and Dahlin [lo] showing that both NeuAc and NeuGc were present in tumour cell glycoproteins, along with the report of Buscher et al [l 11 on the biosynthesis of NeuGc in porcine submaxillary glands and the considerable controversy which has surrounded the oligosaccharide structures of PSM [3 -51 prompted a further investigation.…”
mentioning
confidence: 99%
“…For instance, Rearick et al [q have reported the characterization of porcine submaxillary P-galactoside a2 +3-sialyltransferase, to form the sequence NeuAca(2-t 3)-Galfl(1+3)GalNAc, although this structural element had not been reported in porcine submaxillary mucin (PSM). In addition, a study by Sherblom and Dahlin [lo] showing that both NeuAc and NeuGc were present in tumour cell glycoproteins, along with the report of Buscher et al [l 11 on the biosynthesis of NeuGc in porcine submaxillary glands and the considerable controversy which has surrounded the oligosaccharide structures of PSM [3 -51 prompted a further investigation.…”
mentioning
confidence: 99%
“…When cells are oxidized with periodate and treated with [3H] borohydride, 4 labeled glycoproteins can be seen on subsequent SDS gel electrophoresis which are not labeled if lymph node cells are oxidized by neuraminidase plus galactose oxidase; these are in addition to -20 components labeled in common after either method of oxidation. These 'periodate specific' glycoproteins may contain 4-Oacylated sialic acids which are resistant to neuraminidase but susceptible to periodate [28,29]. Two such glycoproteins on lymph node cells have M,-values of -28 000 and 30 000 which are near that of the small, catalytic subunit of rat y-glutamyltranspeptidase [21]; one of these is sensitive to papain.…”
Section: Resultsmentioning
confidence: 99%
“…This recent discovery goes against one made earlier showing free NeuSAc to be the authentic substrate for the pig mandibular gland enzyme [14]. Due to our interest in the expression of Neu5Gc in malignancy, we have embarked on the study of Neu5Gc biosynthesis in pig mandibular gland.…”
Section: Introductionmentioning
confidence: 97%